1991
DOI: 10.1177/0730888491018003003
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks of Self-Employment

Abstract: This study explores the impact of self-employment on health and argues that favorable aspects of autonomy and self-direction notwithstanding, the self-employed are frequently burdened by uncertainty, market fluctuations, and the threat of loss of assets. These impose considerable stress on the self-employed and induce life-styles and behaviors detrimental to health. The analysis is based on survey and medical data for a sample of men residing in urban areas in Israel. The findings revealed higher levels of beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 25 publications
2
86
1
Order By: Relevance
“…Boyd and Webb (1982), in examining the incidence of 'type A' personalities (thought to be linked to coronary heart disease) among a sample of small business owners, found that stress reduction programmes needed to be implemented for the majority of the sample. In a similar finding, using medical data from a sample of self-employed Israelis, Lewin-Epstein and Yuchtman-Yaar (1991) concluded that there were higher levels of behavioural and psychological risk for self-employed than salaried workers. The choices that older self-employed individuals make about the characteristics of their firm and their work practices may mitigate some of the negative aspects of self-employment.…”
Section: Assumption 3: Being Self-employed Will Be a Positive Work Exmentioning
confidence: 68%
“…Boyd and Webb (1982), in examining the incidence of 'type A' personalities (thought to be linked to coronary heart disease) among a sample of small business owners, found that stress reduction programmes needed to be implemented for the majority of the sample. In a similar finding, using medical data from a sample of self-employed Israelis, Lewin-Epstein and Yuchtman-Yaar (1991) concluded that there were higher levels of behavioural and psychological risk for self-employed than salaried workers. The choices that older self-employed individuals make about the characteristics of their firm and their work practices may mitigate some of the negative aspects of self-employment.…”
Section: Assumption 3: Being Self-employed Will Be a Positive Work Exmentioning
confidence: 68%
“…The autonomy, independence, and ownership central to entrepreneurship may cushion the selfemployed against realizing the full negative impact of high stress, uncertainty, and pressure (Lewin-Epstein and Yuchtman-Yaar 1991). Stressors may be appraised as less threatening by entrepreneurs and may cause less subjective distress (Hausser et al 2010).…”
Section: Entrepreneur Mental Health and Well-beingmentioning
confidence: 99%
“…Similarly, Parker and Rougier (2007) report that older workers with poor health are less likely to move into self-employment in Britain. Self-employment is associated with longer work hours than paid employment and considerable strains (Lewin-Epstein and Yuchtman-Yaar, 1991), which may deter less healthy persons from this choice, in addition to the implications for health insurance costs discussed. The partial effect of spousal poor health is not significant when controlling for the HICD in our estimations.…”
Section: The Effect Of the Health Insurance Cost Differentialmentioning
confidence: 99%